Gardens & beyond / Jardines y más a collection of poems / Colección de poemas - Adams, Elizabeth Anne (Desde Jaén, 2013)
This book is a bilingual collection of writing, including poems and prose originally written in English. It reflects some of the ideas, experiences and impressions of the author gathered over a period of time and grouped together in the loosely thematic chapters in which they seemed to fall most naturally. All the artworks in the book are also the work of the author who has painted in various media for many years. Some of these works have appeared in various exhibitions in Spain and other countries.